Inclusive Crisis Communication During COVID-19: Lessons Learned From the Experiences of Persons With Disabilities in Makassar, Indonesia - Sudirman Karnay; Rahmatul Furqan; Rahman Saeni (Asian Journal for Public Opinion Research)
Persons with disabilities (PwD) are believed to be a group that had a greater risk during the pandemic. While PwD are vulnerable to the spread of COVID-19 due to their high dependence on physical contact, a series of policies restricting public movement during the pandemic had the potential to place PwD in increasingly marginalized situations. This situation reinforces the urgency of crisis communication as one of the critical parts of the COVID-19 response to ensure that all levels and groups of society can accept and understand the flow of information. Using a qualitative approach, this research was conducted through in-depth interviews with PwD age 17-50 in the city of Makassar, Indonesia. The results of this study suggest that crisis communication during the pandemic should involve participatory communication, which focuses on collaboration with empowerment. The PwD communities need to be actively engaged during the communication process of a pandemic crisis to ensure that inclusiveness is always taken into account. During the distribution of information, the relevant health officers or the government at the regional level need to carry out more frequent socialization and special services for PwD based on the characteristics of their disabilities.